Negative electrode-free secondary battery, modified graphite, modified current collector and preparation method thereof

By performing hydrogen-argon mixed gas plasma modification treatment on the graphite, modified graphite suitable for negative electrode secondary batteries was prepared and used to modify current collectors, which solved the problem of unsatisfactory dendrites and large current long cycle performance of negative electrode secondary batteries, and significantly improved the long cycle stability of the battery.

CN119528135BActive Publication Date: 2025-04-25CENT SOUTH UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510075938.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-25
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

The negative electrode current collectors with existing negative electrode-free secondary batteries have dendrite problems and poor long cycle performance of large currents. The existing improvement methods are difficult to fundamentally solve these problems.

Method used

By modifying the graphite with a thickness of 20nm~2μm and a graphitization degree of more than 80% was prepared by modifying the graphite through hydrogen-argon mixed gas plasma, it was prepared and used in a modified current collector without negative electrode secondary batteries. The defects and structure of the graphite surface were optimized, and stable alkali metal nucleophilic sites and interfaces were constructed to improve conductivity.

Benefits of technology

It significantly improves the long cycle stability of the negative electrode-free secondary battery, can cycle more than 1,000 times under high current, and significantly improves the long cycle life of the negative electrode-free secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528135B_ABST
    Figure CN119528135B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of batteries, and specifically relates to a negative electrode-free secondary battery, modified graphite, modified current collector and a preparation method thereof. The preparation method of the modified graphite is as follows: graphite is modified by hydrogen-argon mixed gas plasma to obtain the modified graphite; the graphite has a thickness of 20nm~2μm, a diameter of 0.1~50μm, and a graphitization degree of more than 80%; the power of hydrogen-argon mixed gas plasma modification treatment is 30~250W, and the time is 2~25min. The modification method of the present invention can optimize the defects and structure of the graphite surface, thereby constructing the physical and chemical characteristics of the negative electrode-free secondary battery, thereby significantly improving the long cycle life of the negative electrode-free secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of negative electrode-free secondary batteries, and in particular to the field of negative electrode current collectors of negative electrode-free secondary batteries. Background Art

[0002] The main difference between negative electrode-free alkali metal secondary batteries and conventional secondary batteries with negative electrodes is that there is no active ion embedding material on the negative electrode side, only a negative electrode current collector or some modified current collectors. This can increase the operating voltage and improve the energy density, but there will also be more significant dendrite problems, and its long-range cycle performance is difficult to meet expectations.

[0003] In view of the characteristics of negative electrode-free secondary batteries, the main solution of the prior art is to optimize and improve the current collector. For example, the Chinese patent document with publication number CN119213584A discloses a current collector for a negative electrode-free sodium battery, which is specifically a current collector with a bottom coating formed on the surface, wherein the bottom coating contains carbon nanomaterials, and the carbon nanomaterials contain at least two selected from zero-dimensional carbon materials, one-dimensional carbon materials and two-dimensional carbon materials. The Chinese patent document with publication number CN119213595A discloses a current collector with an interface protective layer. The Chinese patent document with publication number CN118398827A discloses a negative electrode current collector for a negative electrode-free sodium metal battery, which includes a substrate and a functional coating coated on the surface of the substrate; the functional coating includes carbon-based materials with different particle sizes and component gradings. For another example, the Chinese patent document with publication number CN118919734A discloses a negative electrode current collector coated with graphite, carbon nanotubes and a binder for a negative electrode-free sodium metal battery.

[0004] In summary, there are some reports on carbon coating modification of current collectors of negative electrode-free batteries in the prior art, but the existing improvement methods are difficult to fundamentally solve the problems of dendrites and unsatisfactory high current and long cycle performance of negative electrode-free batteries. Summary of the invention

[0005] In order to solve the problems existing in the negative electrode current collector of the existing negative electrode-free secondary battery, the first purpose of the present invention is to provide a method for preparing modified graphite for negative electrode-free secondary battery, aiming to prepare a modified graphite that can adapt to the application characteristics of negative electrode-free secondary battery and can significantly improve the performance of negative electrode-free battery such as long cycle stability.

[0006] The second object of the present invention is to provide modified graphite obtained by the preparation method.

[0007] The third object of the present invention is to provide a negative electrode-free secondary battery comprising the modified graphite and a modified current collector thereof.

[0008] For current collector materials used in negative electrode-free secondary batteries, especially negative electrode-free sodium metal batteries, researchers mostly achieve highly reversible sodium deposition / stripping by constructing sodium-philic metal coatings with alloying ability. However, the price of alloyed coatings is high and difficult to commercialize. In addition, the alloyed coatings will expand in volume during the deposition and stripping process, resulting in the coating falling off. To address this problem, the present invention provides the following improvement means:

[0009] A method for preparing modified graphite for negative electrode-free secondary batteries, wherein the graphite is modified by hydrogen-argon mixed gas plasma to obtain the modified graphite;

[0010] The graphite has a thickness of 20nm~2μm, a diameter of 0.1~50μm, and a graphitization degree of more than 80%;

[0011] The power of hydrogen-argon mixed gas plasma modification treatment is 30~250W, and the time is 2~25min.

[0012] The present invention innovatively selects graphite with specific physical and chemical structural characteristics for the hydrogen-argon mixed gas plasma treatment, and further cooperates with the joint control of plasma power and time, so as to achieve synergy and optimize the defects and structure of the graphite surface, thereby constructing physical and chemical characteristics suitable for negative electrode-free secondary batteries, especially negative electrode-free sodium batteries, for example, constructing structurally stable alkali metal nucleophilic sites and interfaces, improving conductivity; thereby reducing the irreversible loss of alkali metals during the use of negative electrode-free batteries, and optimizing the deposition of alkali metals, thereby significantly improving the long cycle life of negative electrode-free secondary batteries.

[0013] In the present invention, the physicochemical parameters of the graphite, the plasma type, and the combined coordination of plasma power and time are the key to constructing modified graphite with the physicochemical characteristics required for the application of negative electrode-free batteries and improving the performance of negative electrode-free batteries.

[0014] Preferably, the thickness of the graphite is 50 nm to 500 nm, and more preferably 100 nm to 200 nm. The thickness of the graphite is normally distributed within the thickness range.

[0015] The graphite has a diameter of 0.5-20 μm, and a D50 of 2-20 μm, preferably 3-15 μm.

[0016] The graphitization degree of the graphite is 85-95%.

[0017] Studies have shown that the combined control of the preferred graphite thickness, diameter (D50) and degree of graphitization parameters can help further achieve synergy and help further improve the electrochemical performance of the improved graphite in negative electrode-free batteries.

[0018] In the present invention, the hydrogen content in the hydrogen-argon mixed gas is 1-10 vol%, and can further be 3-6 vol%.

[0019] In the present invention, the power of the hydrogen-argon mixed gas plasma modification treatment is 50-200 W, and further 80-120 W. Studies have found that under this preferred process, it is helpful to further optimize the physical and chemical structure of the modified graphite, so that it adapts to the application requirements of the negative electrode-free battery, and helps to improve the electrochemical performance of the negative electrode-free battery.

[0020] In the present invention, the time of the hydrogen-argon mixed gas plasma modification treatment is 3 to 20 minutes, and more preferably 5 to 15 minutes. Studies have shown that under the preferred conditions, it is helpful to further optimize the performance of the prepared modified graphite in the negative electrode-free battery.

[0021] The present invention also provides a modified current collector for a negative electrode-free secondary battery, which comprises a conductive substrate and a modified coating composited on the surface thereof, wherein the modified coating comprises modified graphite prepared by the preparation method of the present invention.

[0022] In the present invention, the modified graphite is used as a modified material for a current collector without a negative electrode, and its role is different from that of a conventional ionic battery with a negative electrode. The role of the modified graphite prepared by the preparation process in the battery without a negative electrode is not to embed and de-embed sodium, but to regulate the uniformity and reversibility of sodium deposition / stripping of the sodium battery without a negative electrode.

[0023] In the present invention, the conductive substrate comprises a planar foil material or a three-dimensional porous material, and the material thereof comprises at least one of copper, aluminum and titanium.

[0024] The modified coating further comprises a binder, wherein the binder comprises at least one of polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber and polyethylene oxide.

[0025] In the modified coating, the content of modified graphite is 85-95wt%.

[0026] The thickness of the modified coating is 500nm~40μm; preferably 0.5~30μm, more preferably 5~20μm, and even more preferably 8~15μm. Studies have shown that at this preferred thickness, the adaptability of the modified coating to the negative electrode-free battery can be further improved, which helps to further improve the reversible homogenization deposition and dissolution of the metal in the negative electrode-free current collector, and helps to further improve its stability.

[0027] The modified current collector of the present invention has a loading amount of modified graphite in the range of 0.1 to 0.8 mg / cm 2 ; further can be 0.25~0.5 mg / cm 2 .

[0028] The present invention also provides a method for preparing the modified current collector for a negative electrode-free secondary battery, wherein the components containing the modified graphite are compounded on a conductive substrate based on a coating or printing process to form a modified coating on the substrate to obtain the modified current collector.

[0029] The present invention also provides a negative electrode-free secondary battery, which comprises the modified graphite described in the present invention. Further, the negative electrode-free secondary battery comprises a positive electrode, a separator and a current collector, wherein the current collector is the modified current collector described in the present invention.

[0030] The negative electrode-free secondary battery of the present invention may include, in addition to the modified current collector of the present invention, other components and structural parts thereof may be known. In addition, in the present invention, the negative electrode-free secondary battery may further be a negative electrode-free sodium secondary battery (also referred to as a negative electrode-free sodium battery) whose performance barrier is difficult to break through by existing means.

[0031] Beneficial Effects

[0032] In view of the problems faced by negative electrode-free secondary batteries, especially negative electrode-free sodium batteries, the present invention innovatively provides a method for preparing modified graphite adapted to the physicochemical characteristics of negative electrode-free secondary batteries, which is based on the physicochemical characteristics of graphite and the combined treatment of hydrogen-argon mixed gas plasma, and further based on the combined control of the power and time of the treatment, so that the physical and chemical characteristics such as defects, structures and interfaces adapted to the negative electrode-free secondary battery can be unexpectedly constructed, and the nucleation, growth and homogenization deposition of the metal of the negative electrode-free secondary battery can be optimized, and the long cycle effect of the negative electrode-free secondary battery can be significantly improved. For example, the negative electrode-free current collector prepared by the process described in the present invention can also be circulated for more than 1,000 cycles under high current. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The scanning electron microscope images of the composite carbon-coated current collector of Comparative Example 1 (commercial carbon-coated aluminum foil) and Example 1;

[0034] Figure 2 This is a cycle stability diagram of a negative electrode-free sodium battery assembled using the composite current collector in Example 1 at a current density of 300 mA / g;

[0035] Figure 3 This is a cycling stability diagram of a negative electrode-free sodium battery assembled using the composite current collector in Example 1 at a current density of 200 mA / g. DETAILED DESCRIPTION

[0036] The technical solution of the present invention is further described below in conjunction with the embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.

[0037] Test conditions

[0038] Preparation of positive electrode sheet (NFPP positive electrode): weigh 0.9 g of sodium iron pyrophosphate (NFPP) positive electrode material and 0.05 g of conductive carbon black, mix and grind for 30 min, then transfer it into a weighing bottle, add 1 g of PVDF / NMP (N-methylpyrrolidone) solution with a PVDF content of 5%, then add 1 ml of NMP, stir for 12 h, and then use carbon-coated aluminum foil as a substrate, place the stirred mixture on it, use a scraper to scrape it evenly, put it in a vacuum drying oven, first dry it at 60 ° C for 6 h, then dry it at 90 ° C for 12 h, then take it out and cut it into a positive electrode sheet with a diameter of 12 mm (also called NFPP positive electrode sheet). The loading amount of the positive electrode material is about 13 ± 1 mg / cm 2 .

[0039] Preparation of negative electrode-free sodium battery electrolyte: Weigh 15.1 g of sodium hexafluorophosphate (NaPF6) and 0.109 g of NaBF4 respectively and dissolve them in 100 ml of diethylene glycol dimethyl ether (DEGDME), add 10 g of molecular sieves to absorb some of the water that may remain in DEGDME, and obtain 0.9M NaPF6+0.1M NaBF4 DEGDME electrolyte. The battery separator is a 19 mm polyethylene separator and a 19 mm glass fiber separator. Use the above-mentioned positive electrode, electrolyte and separator and the corresponding current collector to be tested to assemble a negative electrode-free sodium battery. The voltage range of the negative electrode-free sodium battery test is 1.5~3.9V, and the test temperature is 30 o C.

[0040] Example 1

[0041] Select graphite sheets with a D50 of 3.1 μm and a thickness distribution of 100 nm to 200 nm (particles with a thickness of 150 ± 10 nm account for more than 50%), and a graphitization degree of 92 to 93%. The graphite sheets are bombarded in an argon hydrogen atmosphere (hydrogen content of 5 vol%) plasma at a power of 100 W for 6 minutes, and then the treated powders (modified graphite powder) are used to prepare a negative electrode-free current collector, the steps of which are:

[0042] PVDF with a weight percentage of 10% of modified graphite powder was used as a binder. After being dispersed with NMP, it was scraped onto the surface of aluminum foil and then dried in an oven at 80°C for 12 h to obtain a modified composite current collector (also called a carbon-coated current collector). The coating thickness was 8 μm and the loading was 0.3 mg / cm 2 (SEM after coating Figure 1 It was cut into 14 mm diameter discs, and then assembled with the prepared NFPP positive electrode and the optimized carbon-coated current collector to form a negative electrode-free sodium battery. The optimized composite current collector was tested and the following was obtained: Figure 2 and 3 The results shown in the figure indicate that the use of the modified composite current collector can extend the cycle life of the negative electrode-free sodium battery to more than 1000 times at current densities of 300 mA / g and 200 mA / g, with the capacity retention rates of 90.7% and 92.4% after 200 cycles, respectively, and the modification effect is obvious.

[0043] Comparative Example 1

[0044] Compared with Example 1, the difference is that the following current collectors are used as negative electrode current collectors, and the experimental groups are:

[0045] Group A: carbon-coated aluminum foil, which is different from Example 1 only in that the graphite is not subjected to the hydrogen-argon plasma treatment;

[0046] Group B: The negative electrode current collector is aluminum foil without modified coating;

[0047] Group C: The negative electrode current collector is copper foil;

[0048] Group D: The negative electrode current collector is titanium foil;

[0049] Each control group was heated at 30°C, 200 mA g -1 The results are shown in Table 1.

[0050]

[0051] It can be seen from Table 1 that the effects of each comparison group are significantly different from those of Example 1.

[0052] Example 2

[0053] Compared with Example 1, the only difference is that the thickness of the graphite before modification is 0.1-0.2 μm (the proportion of particles with a thickness of 150±10 nm is more than 50%), D50 is 6.5 μm, and the degree of graphitization is 90-91%; the plasma process of Example 1 is used for treatment and modification, and a negative electrode-free current collector is prepared according to the method of Example 1, wherein the thickness of the modified coating is further improved, and the negative electrode-free battery is assembled according to the method of Example 1. Subsequently, the stability test is evaluated by cycling 200 times at a current density of 200 mA / g, and the results are shown in Table 2.

[0054]

[0055] It can be seen from Table 2 that the thickness of the modified coating is controlled between 0.5 and 30 μm, preferably between 5 and 20 μm, and further between 8 and 15 μm, which can unexpectedly enhance the performance of the modified coating in the negative electrode-free sodium battery and improve the cycle stability under high current.

[0056] Example 3

[0057] Compared with groups 1-3 of Example 2, the only difference is that the thickness of the graphite sheet is changed, and the other operations, parameters and tests are the same as those of Example 2. The results are shown in Table 3:

[0058]

[0059] Note: The thickness of the selected graphite sheets is normally distributed within the thickness range described above, among which the graphite sheets with a thickness near the median [(upper limit thickness h1 + lower limit thickness h2) / 2±10%] account for more than half.

[0060] It can be seen from Examples 2 and 3 that by controlling the thickness of graphite, especially controlling the thickness of graphite within 50nm~500nm, especially controlling it within 100~200nm, a better graphite modification effect can be obtained, and a better negative electrode-free sodium battery performance can be obtained.

[0061] Example 4

[0062] Compared with groups 1-3 of Example 2, the only difference is that the diameter range and D50 of the graphite before modification are changed, and the other operations, parameters and tests are the same as those of Example 2. The results are shown in Table 4:

[0063]

[0064] It can be seen from Examples 2 and 4 that by controlling the particle size of graphite, especially controlling the D50 of graphite to 2-20 μm, preferably 3-15 μm, a better graphite modification effect can be obtained, and a better negative electrode-free sodium battery performance can be obtained.

[0065] Example 5

[0066] Compared with groups 1-3 of Example 2, the only difference is that the graphitization degree of the graphite before modification is changed, and the other operations, parameters and tests are the same as those of Example 2. The results are shown in Table 5:

[0067]

[0068] It can be seen from Examples 2 and 5 that by controlling the graphitization of graphite to be above 85%, preferably above 90%, a better graphite modification effect can be obtained, and a better negative electrode-free sodium battery performance can be obtained.

[0069] Example 6

[0070] Compared with groups 1-3 of Example 2, the only difference is the hydrogen-argon mixed gas plasma power, and the other operations, parameters and tests are the same as those of Example 2. The results are shown in Table 6:

[0071]

[0072] It can be seen from Examples 2 and 6 that when the processing power is 50~200W, preferably 80~120W, a better graphite modification effect can be obtained, and a better negative electrode-free sodium battery performance can be obtained.

[0073] Example 7

[0074] Compared with groups 1-3 of Example 2, the only difference is the hydrogen-argon mixed gas plasma treatment time, and other operations, parameters and tests are the same as Example 2. The results are shown in Table 7:

[0075]

[0076] It can be seen from Examples 2 and 7 that when the treatment time is 3 to 20 minutes, preferably 5 to 15 minutes, a better graphite modification effect can be obtained, and a better negative electrode-free sodium battery performance can be obtained.

[0077] Comparative Example 2

[0078] Compared with 1-3 of Example 2, the only difference is that the plasma position is changed to atmospheric atmosphere plasma, oxygen atmosphere plasma, and nitrogen atmosphere plasma; its operation, parameters and tests are the same as those of Example 2, and the results are shown in Table 8.

[0079]

[0080] It can be seen from Example 2 and Comparative Example 2 that the use of the plasma described in the present invention for treatment can unexpectedly achieve synergy and can significantly improve the long cycle performance of the prepared modified graphite material in a negative electrode-free battery.

Claims

1. A modified current collector for a negative electrode-free secondary battery, characterized in that: It comprises a conductive substrate and a modified coating compounded on the surface thereof, wherein the modified coating comprises modified graphite; The preparation method of the modified graphite is as follows: graphite is modified by hydrogen-argon mixed gas plasma to obtain the modified graphite; The graphite has a thickness of 20nm~2μm, a diameter of 0.1~50μm, and a graphitization degree of more than 80%; The power of hydrogen-argon mixed gas plasma modification treatment is 30~250W, and the time is 2~25min.

2. The modified current collector for a negative electrode-free secondary battery according to claim 1, characterized in that: The graphite has a thickness of 50nm-500nm, a diameter of 0.5-20μm, a D50 of 2-20μm, and a graphitization degree of 85-95%.

3. The modified current collector for a negative electrode-free secondary battery according to claim 1, characterized in that: The hydrogen content in the hydrogen-argon mixed gas is 1-10 vol%.

4. The modified current collector for a negative electrode-free secondary battery according to claim 1, characterized in that: The power of hydrogen-argon mixed gas plasma modification treatment is 50~200 W; the modification treatment time is 3~20 minutes.

5. The modified current collector for a negative electrode-free secondary battery according to any one of claims 1 to 4, characterized in that: The conductive substrate comprises a planar foil material or a three-dimensional porous material, and the material thereof comprises at least one of copper, aluminum and titanium.

6. The modified current collector for a negative electrode-free secondary battery according to claim 1, characterized in that: The modified coating further comprises a binder, wherein the binder comprises at least one of polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber and polyethylene oxide; In the modified coating, the content of modified graphite is 85-95wt%; The thickness of the modified coating is 500 nm~40 μm; In the modified current collector, the loading amount of modified graphite is 0.1~0.8 mg / cm 2 .

7. A method for preparing a modified current collector for a negative electrode-free secondary battery according to any one of claims 1 to 6, characterized in that: The modified current collector is prepared by compounding the components containing the modified graphite on a conductive substrate based on a coating or printing process to form a modified coating on the substrate.

8. A negative electrode-free secondary battery, characterized in that: Comprising a positive electrode, a separator and a current collector, wherein the current collector is the modified current collector according to any one of claims 1 to 6; The negative electrode-free secondary battery is a negative electrode-free sodium secondary battery.

Citation Information

Patent Citations

  • Negative current collector, preparation method thereof and non-negative sodium metal battery

    CN118398827A

  • Negative current collector for negative-electrode-free sodium metal battery as well as preparation method and application of negative current collector

    CN118919734A

  • Current collector, application thereof, secondary battery, battery module, battery pack and electric device

    CN119213584A

  • Current collector, secondary battery, battery module, battery pack, and electric device

    CN119213595A

  • Graphite purification method and purification device

    CN113387354A